Load case selection for finite-element simulations of wind turbine pitch bearings and hubs - M. Stammler; F. Schleich (Wind Energy Science)
Finite-element simulations of large rolling bearings and structural parts are an indispensable tool in the design of wind turbines. Unlike simpler structures or smaller bearings in rigid environments where analytical formulas suffice, wind turbine components require a more comprehensive approach. This is because analytical formulas often fall short in predicting load distributions and stresses, leading to inadequate designs. However, due to the complexity of the finite-element models and number of operational load cases involved, it is necessary to strike a balance between achieving realistic results and keeping computational times manageable. This study focuses on the selection of load cases for simulations of pitch bearings and hubs of wind turbines. The models for these contain the hub, the pitch bearings, the inner parts of three blades, and any necessary interface parts. The simulation results allow for the calculation of static and fatigue strength. Given the complexity of the problem, with each rotor blade having 6 degrees of freedom, 5 types of loads, and a pitch angle, their potential combinations would result in an unmanageably high number of required simulations. The present work assumes that binning of 1 or more degrees of freedom into sufficiently small bins results in the other degrees of freedom showing negligible variation. Defining the values for these binned degrees of freedom thus gives the values for the others and reduces the number of combinations drastically. The validity of this approach is verified by the standard deviations of the unbinned degrees of freedom and by exemplary stress calculations of a pitch bearing ring. The blade's azimuth angle and bending moments of one blade root allow determining the loads at all three blade roots and thus the derivation of stress time series with 384 simulations of a full rotor with a reasonable degree of confidence.